Use of Polyglycolic Acid Mesh in Extreme Preterm Premature Rupture of Membranes (PPROM) - İdris Koçak; Ayşe Özdemir; Pervin Karlı (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2018)
Introduction: Extreme Preterm Premature Rupture of Membranes (PPROM) is a condition that increases maternal, fetal and neonatal morbidity and mortality to a large extent. In this study, we aimed at prolonging the gestational periods of 3 patients with extreme PPROM by way of sealing the cervical os using PGA mesh and fibrin glue to stop physical amniotic discharge.  Materials and Methods: We used the system based on fixing a piece of PGA (Polyglycolic Acid - NeoveiL absorbable polyglycolic acid felt) mesh on cervical os in patients with extreme PPROM. A fibrin glue solution (TISSEEL Lyo) was heated in a Fibrinotherm device to be used for fixing the PGA mesh. The risk of infection was monitored in the patients through measurements of fever and C reactive protein (CRP) levels and hemogram parameters. For infection prophylaxis, each patient was given antibiotherapy, and after the 24th gestational week, 24 mg of betamethazone in 24-hour intervals and ultrasonographic assessments and contraction monitoring were carried out twice a week. Results: The gestational periods of all the patients we treated were prolonged at least a month. No maternal or fetal infections were seen in any of the patients. One of the patients had a delivery at her gestational week 28 and her baby is still alive. The other 2 patients had deliveries after 26 gestational weeks and 3 days and 29 gestational weeks and 5 days, the former infant dying immediately after birth and the latter a week after birth.  Conclusion: The management of extreme PPROM is still a controversial issue worldwide. Its high maternal and fetal morbidity impedes adaptation of a certain treatment approach. We presented in our study a different way of managing extreme PPROM cases. Our rate of success is around 33%. We think that broader series of studies are needed to assess the reliability and effectiveness of this approach.